Kant: Friend or Foe of the Believer? Plantinga and Other American Christian Responses to Kant's Epistemology - Andrew Gustafson (حکمت و فلسفه, 2005)
Plantinga, Wolterstorff and Westphal are three eminent Christian Philosophers in the United States today. This paper will examine Plantinga, Wolterstorff, and Westphal's response to Kant's anti-realist epistemology. While perhaps many Christian philosophers doing philosophy of religion in the United States follow the common-sense realism of Thomas Reid, some philosophers, like Merold Westphal, support a Christian-Kantian-Creative-Anti-Realism. I will criticize Plantinga's and Wolterstorff's position, and support Westphal's, arguing that Kant's epistemology does not harm religious belief but in fact supports it